Why do Customers Get more than They Need? How Organizational Culture Shapes Product Capability Decisions. (January 2013) - Lukas, Bryan A.; Whitwell, Gregory J.; Heide, Jan B.
The capability level of a product that a firm provides to a customer is an important marketing decision. In the extant literature, the normative heuristic for this decision is one of matching—of providing product capability levels that meet customer needs. However, industry evidence suggests that supplier firms routinely make product decisions that lead to "overshot" customers, whereby customers receive products with capabilities that exceed their requirements. The authors demonstrate how a supplier firm's organizational culture can cause overshooting scenarios and how these effects can be attenuated to the extent that the focal firm's basic values also reflect a customer orientation.